The post-enlargement migration experience in the Baltic labor markets - Mihails Hazans; Kaia Philips (Institute for the Study of Labor (IZA), 2011)
We use Lithuanian, Latvian and Estonian LFS data (2002-2007) complemented with several other surveys to compare the profile of Baltic temporary workers abroad before and after EU accession with that of stayers and return migrants. Determinants of migration and return, as well as selection issues are discussed. Post-enlargement migrants from all three countries were significantly less educated than stayers. After accession, medium-educated workers were most likely to move, other things equal, and human capital became increasingly less pro-migration over time. Return migrants differ from all movers in many ways and, in particular, are more educated. Although brain drain was not a feature of post-accession Baltic migration, brain waste was: during 2006-2007, the proportion of overqualified among high-educated movers ranged from five out of ten for Latvia to seven out of ten for Lithuania, but it was around one fifth among high-educated stayers in all three countries. We find that the free movement of labor partially introduced in 2004 (and expanded in 2006) for EU citizens, although excluding Baltic non-citizens, brought about significant changes in how ethnicity and citizenship affect workers' mobility. We conclude by discussing migration perspectives in the context of recession.
urn:nbn:de:101:1-201108093054
Keywords: J61; J15; 330; migration; EU enlargement; Baltic countries; return migrants; ethnic minorities